Investigation of low- and high cycle fatigue in Al 2024-T4 alloy - Kłysz, Sylwester Bogumił (Technical Sciences, 2021)
The article presents the results of low- (LCF) and high-cycle fatigue (HCF) analyses of 2024-T4 aluminum alloy which is used in aircraft construction, mainly for highly loaded structural components, including for plating, fuselage frames and rotor blade girders in helicopters. The alloy is used in structures where a high strength-to-weight ratio and high fatigue resistance are required. However, the alloy is poorly weldable and has low corrosion resistance. The tests were performed on hourglass and cylindrical samples with parallel and perpendicular orientation relative to the rolling direction. Samples for analysis were obtained from the production line of PZL-130 Orlik TC-II trainer aircraft. The results of the analysis were described by Manson–Coffin and Morrow equations.